Smart School Management System of Presence Monitoring Teacher as A Realtime with Rad (Rapid Application Development) Method at Khadijah High School Surabaya - Rahmawati Febrifyaning Tias; Mas Nurul Hamidah; Arif Arizal; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2021)
This research create an application for monitoring the presence of teachers when carrying out teaching activities in real time at Khadijah High School Surabaya. The method that will be used in making this application is to use the RAD (Rapid Application Development) method. The RAD method is an application development process based on prototyping, iteration, and repeated feedback. That way the applications that are made can be developed and repaired quickly and are in accordance with the needs and developments of the super-fast digital world. The process of testing this application is carried out by simulating the teaching and learning process carried out by the teacher and monitored directly by the principal in real time. Smart school management system application as a real-time monitoring of teacher attendance using the RAD (Rapid Application Development) method at SMA Khadijah Surabaya. The results of this study are very useful for school principals to monitor teachers in teaching and learning activities at Khadijah High School Surabaya and also make it easier for teachers to make attendance at teaching and learning activities every time.